Design of mathematics learning by using role playing to investigate the self-efficacy ability. (February 2019) - Somakim; Darmawijoyo; Eliyati, N; Yulianita
Abstract: This study aims to determine how the use of role playing learning models in mathematics lessons fosters the ability of self-efficacy of high school students. This article is part of a large study with the title Combinatoric Material Learning Design Using Indonesian Realistic Mathematics Education to See Students' Self-efficacy Ability. Mathematics subject matter which is the object of research is the topic of combinatorics. The research method used is design research, consists of three stages: introduction, field trial and analysis. Data collection techniques were obtained through video recordings, questionnaires, and interviews. The subjects of the study were students of the SMAN 15 Palembang. The data analysis technique is done by describing the questionnaires filled by students. The results showed that by using the context of role playing, it could foster the ability of self-efficacy in high school students with good categories.